2019
DOI: 10.3390/metabo9100216
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Pyruvate Kinase Affects Glucose-Dependent Carbon Catabolite Repression in Bacillus subtilis

Abstract: Pyruvate is a key intermediate of diverse metabolic pathways of central carbon metabolism. In addition to being the end product of glycolysis, pyruvate is an essential carbon distribution point to oxidative metabolism, amino acid and fatty acid syntheses, and overflow metabolite production. Hence, a tight regulation of pyruvate kinase (Pyk) activity is of great importance. This study aimed to analyze targeted metabolites from several pathways and possible changes in Bacillus subtilis lacking Pyk. Wild type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…4 c). CcpA, the global transcription factor of Bacillus subtilis , binds to the phosphorylated cofactor HPr to form a ternary complex that represses other carbon-derived catabolite related gene expression during mixed sugar fermentation (Sousa et al 2019 ). It was suggested by Lu Lin et al ( 2020 ) that CCR could be relieved by inhibiting the activities of two enzymes, CcpA (the global transcription factor of Bacillus subtilis ) and HPrK.…”
Section: Discussionmentioning
confidence: 99%
“…4 c). CcpA, the global transcription factor of Bacillus subtilis , binds to the phosphorylated cofactor HPr to form a ternary complex that represses other carbon-derived catabolite related gene expression during mixed sugar fermentation (Sousa et al 2019 ). It was suggested by Lu Lin et al ( 2020 ) that CCR could be relieved by inhibiting the activities of two enzymes, CcpA (the global transcription factor of Bacillus subtilis ) and HPrK.…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis reached its first OTR peak of 25 mmol/L/h after 3 h, when grown on glucose‐enriched LB medium. Following the first OTR peak, growth on the LB‐glucose medium displayed three other peaks after 5, 9, and 16 h. As Bacillus subtilis is known to produce acetate, acetoin, and 2,3‐butanediol at excess glucose concentrations, 55–57 different respiratory activities may indicate a change in substrate and overflow metabolite consumption. Growth on the complex components of the LB‐glucose medium led to ammonium ions being release, 6 causing the pH to be increased to 7.5 (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…This OTR peak was followed by a second OTR peak of 14.5 mmol/L/h. At this highest CSL concentration, B. subtilis is likely to have produced its known overflow metabolites acetate, acetoin, and 2,3-butanediol, [55][56][57] which are then consumed as indicated by the second peak (Figure 5a).…”
Section: Influence Of Different Glucose/csl (G/g) Ratios On Bacillus ...mentioning
confidence: 99%
“…Since previous studies on CCR in Bacillus showed that cre negatively regulates genes related to carbohydrate catabolism ( Sousa et al, 2019 ), mutation of cre could potentially disrupt secondary pathways, and lead to a significant increase in extracellular excretion. When we incubated the mutant LG3145 strain on LB agar, colonies were more adhesive and pigmented under the naked eye, with fuzzy edges, whereas WT colonies appeared smooth, white, and with distinct edges ( Supplementary Figures S6A, 6B ).…”
Section: Resultsmentioning
confidence: 99%